75 floral blocks to knit : beautiful patterns to mix & match for afghans, throws, baby blankets, & more - Stanfield, Lesley (St. Martin's Griffin, 2013)
Another great book for knitters and crafters on the go, the second book in our Floral Blocks series features a wonderful collection of knitted floral-themed blocks of all shapes and sizes. Bestselling author Lesley Stanfield offers a variety of square, triangular, diamond, and hexagonal-shaped blocks that knit up quickly, are portable, and wonderfully versatile. Using a variety of knitting techniques from colorwork, to raised effects, to open, lacy stitches, there's a bouquet of blocks to knit that can be easily incorporated into delightful projectsu2014from patchwork throws to a lacy vest, there's something to delight every knitter. All the blocks are a breeze to make while following the written instructions which are accompanied by symbols indicating the direction of knitting, skill level, and color charts. And like previous books in the series, 75 Floral Blocks to Knit contains a refresher course on basic knitting techniques is included, along with an overview of different methods for joining blocks. The creative projects section will guide and inspire you to mix and match the wide range of designs into endless combinations to assemble a flourishing garden of projects featuring daisies, sunflowers, pansies, lilies, rosebuds, and more!